Exploring the Impact of Mini Labs and Hands-On Learning in Magnetism on Students Cognitive and Critical Thinking Abilities - Qamila*, Fairus; Sinaga, Parlindungan; Winarno, Nanang; Arisna, Definda Putri (Jurnal Pendidikan Sains Indonesia, 2025)
Many students struggle to understand abstract physics concepts such as magnetism due to limited practical engagement and conventional teaching methods. This study aims to explore the impact of a mini lab and hands-on learning approach to magnetism on students cognitive and critical thinking abilities (CTA). The study employed a pre-experimental one-group pretest-posttest design and was conducted in a junior high school in South Tangerang City, with 25 ninth-grade students serving as research subjects. Learning took place through six mini lab stations presenting different topics, as well as hands-on activities involving the design of a simple compass. Data were collected through cognitive and CTA tests, as well as documentation from the students' worksheets and KWL (know-want-learned) charts. The analysis revealed a significant increase in cognitive abilities, with moderate gain scores. Conversely, the increase in CTA was not statistically significant, with low gain scores. Limited time and inadequate conceptual reflection space were the main factors. These findings suggest that mini labs and hands-on approaches effectively build conceptual understanding, but strategies are needed to optimize the development of students' CTA